Sectorial Analysis of the U.S. and China Trade Conflict - Okafor, Anthony; Agbai, Edward; Egbedoyin, Funminiyi (European Scientific Journal, ESJ, 2021)
The impact of the U.S - China trade conflict extends beyond both nations’ economies to the economies of trade allies and non-trading partners caught in the web of the trade impasse. This paper conducts a sectoral analysis of the trade conflict on the U.S economy using the manufacturing, agriculture, and technology sectors as metrics. We explore data from the databases of the U.S Census Bureau and the U.S Bureau of Economic Analysis from 2001 to 2019. The trade conflict has led to a significant reduction in trades between both nations. The 25% counter tariff imposed by China reduced U.S exports by 30 billion between 2018 and 2019. Primary income receipts declined 10%, and secondary income receipts declined further in the negative territory. China’s counter-tariffs increased component costs for the U.S automobile industry, leading to a reduction in the number of new and used vehicles sold during the period. We identify an incentive-driven trade policy framework against the current punitive stance, the resumption of trade negotiations, and leveraging the WTO’s instrumentality as measures to resolve the current trade conflict.